2020
DOI: 10.1093/conphys/coaa029
|View full text |Cite
|
Sign up to set email alerts
|

Zinc concentrations in teeth of female walruses reflect the onset of reproductive maturity

Abstract: Age at maturity is an important parameter in many demographic models and, for some species, can be difficult to obtain using traditional methods. Incremental growth structures act as biological archives, recording information throughout an organism’s life and possibly allowing for the reconstruction of life history events. Concentrations of zinc (Zn) in animal tissues are known to be linked to life history, physiology and reproduction and may be retained in incremental growth structures. This study reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…An update to Taylor and Udevitz (2015) found that the walrus population underwent a lesser population decline from 1980s to present and that the population could have reached an equilibrium by 2015 ( Taylor et al , 2018 ). Further, the age of sexual maturity in females potentially plateaued in the late 2000s indicating that a walrus carrying capacity could have been reached by the late 2000s ( Clark et al , 2020 ). Overall, progesterone and estradiol concentrations are low in the modern walrus population ( Table 1 ), lending more evidence to the population possibly producing fewer calves ( Garlich-Miller et al , 2006 ), and/or the population is nearing carrying capacity ( Udevitz et al , 2017 ; Clark et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An update to Taylor and Udevitz (2015) found that the walrus population underwent a lesser population decline from 1980s to present and that the population could have reached an equilibrium by 2015 ( Taylor et al , 2018 ). Further, the age of sexual maturity in females potentially plateaued in the late 2000s indicating that a walrus carrying capacity could have been reached by the late 2000s ( Clark et al , 2020 ). Overall, progesterone and estradiol concentrations are low in the modern walrus population ( Table 1 ), lending more evidence to the population possibly producing fewer calves ( Garlich-Miller et al , 2006 ), and/or the population is nearing carrying capacity ( Udevitz et al , 2017 ; Clark et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This, along with their negative correlations with mean walrus population estimates, potentially indicates low calf production and a population that may be approaching carrying capacity. It is important to note that the current carrying capacity may be lower relative to historical carrying capacity due to climate change related stressors ( MacCracken, 2012 ; Clark et al , 2020 ). Bone steroid hormones could also be useful for assessing physiological responses to climate change in other pagophilic marine mammals, including polar bears and ice seals.…”
Section: Discussionmentioning
confidence: 99%
“…and N.M.), and the positions of these growth layers were revisited on at least two additional days to confirm their positions on the laser ablation transect. Estimates of overall age (age at death) were also generated for each animal using the methods described in Clark et al (2020b), and median age estimates were used to calculate approximate birth year for all animals examined in this study (Table S1).…”
Section: Weaning Age Assignmentmentioning
confidence: 99%
“…The shaded area represents the weaning period, from its beginning with the first incorporation of non-milk foods, to its end, when the offspring consumes an entirely non-milk diet walruses and those in the published literature for primates. This type of spatially explicit, high-resolution analysis of trace element concentrations in animal tissues has already provided information about animal physiology, life history and migratory movements (Alibert & McCulloch, 1997;Clark et al, 2020b;Outridge & Stewart, 1999;Secor, Henderson-Arzapalo, & Piccoli, 1995;Thompson et al, 2003), and will no doubt continue to prove valuable. Future research pairing trace element measurements with other techniques, such as stable isotope or hormone analyses, may be particularly fruitful.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…limited (although rapidly increasing: e.g., Clark et al, 2020a;Newham et al, 2020a), by the fact that the latter do not leave a clear fossilized record. Nonetheless, understanding the evolution of life history traits in relation to ecological variables can have implications not only for primate behavioral ecology but also for primate conservation (Brockman & Van Schaik, 2005) and human evolution.…”
mentioning
confidence: 99%